O Warunkach Koniecznych i Dostatecznych Optymalizacji Sprężystych Płyt Siatkowych na Minimum Odkształcalności - Gierliński, J. (Engineering Transactions, 1973)
In the paper introduced is the solution of the problem of lattice plates optimalization of rods. with arbitrary transverse cross-sections. As 3 criterium of optimalization of plates a minimum elastic deformation was accepted. On the basis of a continuous model of fibrous center, formulated was the problem of variational optimalization, which was then dissolved in general manner, giving the necessary and sufficient conditions of optimalization of lattice plates. The performed solution was analized with reference to the plates of rods not suffering the shape deformation.